Identifikasi dan Penyusunan Faktor Kepuasan Pelayanan di UPT Perpustakaan Pusat Universitas Sebelas Maret Berdasarkan Persepsi Pengunjung - Iftadi, Irwan; Damayanti, Retno Wulan; Puspitasari, Hangganis Septiastuti (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2012)
The evaluation of UNS Central Library service satisfaction has not been considering visitors factor. Meanwhile, visitors are the main consumers of UNS Central Library. The purpose of this study is to identify and organize factors influencing UNS Central Library service satisfaction based on visitors perceptions. The study consisted of four stages, which are identification of initial attributes, confirmation of initial attribute list, confirmation of attributes, and grouping of attributes. The study has suggested 25 attributes considered important by respondent. Those 25 attributes are clustered into four factors. Ten attributes into the service affect factor, seven attributes into the library as place factor, three attributes into the personal control factor, and five attributes into the information access factor.